Designing an organizational engagement model using structural equation modeling: case study of National Iranian Oil Company - Vahideh Delbahari; Iraj Soltani; Akbar Etebarian Khorasgani (Problems and Perspectives in Management, 2019)
Today’s organizations need energetic and engaged employees, those who are interested in their jobs. Generally, the engaged ones love their job and do their job tasks well. If there is no engagement in the organizations, the organization is encountered with serious problems in this ground. This study aims to design engagement assessment model in the organizations and its applied purpose is creating new theoretical basics in the maturity of engagement in the organization and this helps the organizations for better perception and consistency of organizational goals with the goals of employees. The employees of the National Iranian Oil Company constituted the population for this research. The National Iranian Oil Company was selected as the context, because employee engagement has emerged as a critical problem confronting this sector. 356 employees of this company were selected by simple random sampling method and data were collected using a questionnaire. The researcher attempts to answer the question how we can design an engagement assessment model in the organizations. The different dimensions of engagement are identified at individual and organizational levels and then based on the findings, the employees are classified based on the individual and organizational engagement and the results of this study can help the researchers for better recognition of this internal variable and this helps the better understanding of researchers to use it.